Analisis Struktur Modal Dalam Meningkatkan Profitabilitas Pada PT. Aneka Gas Industri TBK - Nova Andani; Nurbaiti Nurbaiti; Arnida Wahyuni Lubis (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
PT. Aneka Gas Industri Tbk is the largest industrial gas company in Indonesia. Profitability is the company's ability to generate profits by using the company's capital. Companies with high profitability show that the company's management is able to optimize capital in generating profits. This study aims to analyze how the capital structure as measured by Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) in increasing profitability as measured by Return On Asset (ROA) and Return On Equity (ROE) at PT. Aneka Gas Industri Tbk. The type of research used is descriptive quantitative and secondary data sources. The results of this study are the company's capital structure has not been able to increase ROA and ROE at PT. Aneka Gas Industri Tbk. The DER and DAR values ​​are still above the industry average, which indicates that the company is entirely financed by creditors, which can cause greater risk for the company. After analysis, it is known that the decline in the value of ROA is due to ineffective asset management, this can be seen from the high number of company assets but low profits. The decrease in return or ROE indicates that the company is not effective in using the company's equity so that the increase in net income is smaller than the increase in company equity.